Analisis Kelayakan Usaha Pada Industri Kecil Kripik Tempe Di Kecamatan Ngawi Kabupaten Ngawi - Atik Pita Riyani; Muhammad Yasin (Jurnal Manajemen Kreatif dan Inovasi, 2023)
Efforts to improve the Indonesian economy are important, because Indonesia has great economic potential. Because if the economy increases, the standard of living and conditions of society will also increase. The purpose of this study was to find out how the business feasibility of small tempe chip industries in Ngawi District, Ngawi Regency. The informants in this study were the owners of a small tempe chip industry in Ngawi District, Ngawi Regency. The number of informants in this study were 6 small business owners of tempeh chips. Research on small industrial enterprises uses analytical methods including ROI, R/C, and B/C. The method of data collection was carried out using editing and tabulation techniques. For the results of the research that has been done, it shows that the average cost of production incurred by the small tempe chip industry in Ngawi District, Ngawi Regency is Rp. 15,065,971/month, while the average income in the small tempe chip industry is IDR 42,666,667. the average result of the feasibility analysis of small tempe chip industry businesses in Ngawi District, Ngawi Regency in one month of production is that the ROI is declared feasible because a result of 3.84% is said to be feasible because ROI > 1. On average the results of R/C on business feasibility that is equal to 3.90 R/C ratio is said to be feasible. Whereas for the average B/C ratio analysis method, it is obtained at 2.01, so the business is feasible to run because B/C> 1.